PENGARUH LINGKUNGAN SEKOLAH DASAR ISLAM TERPADU TERHADAP NILAI RELIGIUS SISWA - Bachtian Rudin, Raka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The school environment plays a crucial role in shaping students' religious values through role models, habits, social interactions, and a school culture based on Islamic values. Studying the influence of the integrated Islamic elementary school environment is crucial as a basis for strengthening religious character education in elementary schools. This study aims to analyze the influence of the integrated Islamic elementary school environment on elementary school students' religious values. This study used a quantitative approach with a survey method involving 35 students. Data were collected using a questionnaire and analyzed using prerequisite tests, Pearson correlation, and simple linear regression. The results showed a very strong positive relationship between the integrated Islamic elementary school environment and students' religious values, with a correlation coefficient of 0.823. The regression analysis showed a coefficient of determination of 0.677, or 67.7%. The effect was significant, with a ttest of 8.313 > ttable of 2.035 and p < 0.001. Thus, the integrated Islamic elementary school environment has a positive and significant influence on students' religious values. Strengthening a religious school culture, providing role models, and instilling habits are important aspects in supporting the development of students' religious character.